2022
DOI: 10.1093/beheco/arac048
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of care by breeders and helpers in the cooperatively breeding long-tailed tit

Abstract: In species with biparental and cooperative brood care, multiple carers cooperate by contributing costly investments to raise a shared brood. However, shared benefits and individual costs also give rise to conflict among carers conflict among carers over investment. Coordination of provisioning visits has been hypothesized to facilitate the resolution of this conflict, preventing exploitation, and ensuring collective investment in the shared brood. We used a 26-year study of long-tailed tits, Aegithalos caudatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…On current evidence, turn‐taking seems common in birds (e.g. Halliwell et al., 2022; Johnstone et al., 2014; Koenig & Walters, 2016; Savage et al., 2017; but see Khwaja et al., 2017) and may therefore afford fitness benefits in many species, including both biparental and cooperative breeding systems. Future research on environmental (e.g.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On current evidence, turn‐taking seems common in birds (e.g. Halliwell et al., 2022; Johnstone et al., 2014; Koenig & Walters, 2016; Savage et al., 2017; but see Khwaja et al., 2017) and may therefore afford fitness benefits in many species, including both biparental and cooperative breeding systems. Future research on environmental (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, birds usually need to forage away from the nest before coming back to feed the brood, making alternated visits by different carers more likely than consecutive visits of the same individual ('passive turn-taking'; Savage et al, 2017). The few relevant studies currently available confirmed that alternation can occur in groups with more than two carers (Halliwell et al, 2022;Koenig & Walters, 2016;Savage et al, 2017), supporting the view that cooperative care results from individuals responding to the investment of others and adjusting their own behaviour accordingly. An interesting exception is that of the rifleman Acanthisitta chloris, where carers do not coordinate, possibly because of the low level of potential conflict over nestling care in this species (Khwaja et al, 2017).…”
Section: Introductionmentioning
confidence: 92%